PotenziaMente 2.0. Developing numeracy in primary schools through computer games - Roberto Trinchero (Firenze University Press, 2016)
Research in neuroscience and psychology of learning suggests the existence of inborn "number sense", localized in specialized brain structures that deal with interpreting the world in terms of numbers. However in the common sense of young people and adults are still strong beliefs that mathematics is something of abstract, difficult and far away from everyday life. How is it possible to build numeracy in children using these innate capacities and fostering the development of the right attitudes towards the mathematical knowledge? The article describes the possible impact on educational practices of the research about the number sense and the role of executive functions in mathematical reasoning. It presents the basic principles of a collection of computer games freely available online (PotenziaMente 2.0) designed specifically to develop lexical, semantic and syntactic aspects of numeracy and increasing the use of executive functions in typical mathematical problem solving for primary school.   PotenziaMente 2.0. Costruire la numeracy nella scuola primaria attraverso il gioco computerizzato La ricerca in neuroscienze ed in psicologia dell'apprendimento suggerisce già da tempo l'esistenza di un "senso del numero" innato, localizzato in strutture cerebrali specializzate che si occupano di interpretare il mondo in termini numerici. Eppure nel senso comune di giovani e adulti permangono credenze che vedono la matematica come un qualcosa di astratto, difficile e lontano dalla vita quotidiana. Come è possibile costruire la numeracy nei bambini sfruttando queste capacità innate e favorendo lo sviluppo dei giusti atteggiamenti verso il sapere matematico? L'articolo descrive le possibili ricadute educative della ricerca sul senso del numero e sul ruolo delle funzioni esecutive nel ragionamento matematico. Partendo da queste risultanze, presenta poi i principi alla base di una collezione di giochi computerizzati liberamente fruibili online (PotenziaMente 2.0) concepiti per sviluppare gli aspetti lessicali, semantici e sintattici della numeracy e potenziare l'uso delle funzioni esecutive su problemi matematici tipici della scuola primaria.